2018
DOI: 10.1371/journal.pntd.0006525
|View full text |Cite
|
Sign up to set email alerts
|

Viral immunogenicity determines epidemiological fitness in a cohort of DENV-1 infection in Brazil

Abstract: The dynamics of dengue virus (DENV) circulation depends on serotype, genotype and lineage replacement and turnover. In São José do Rio Preto, Brazil, we observed that the L6 lineage of DENV-1 (genotype V) remained the dominant circulating lineage even after the introduction of the L1 lineage. We investigated viral fitness and immunogenicity of the L1 and L6 lineages and which factors interfered with the dynamics of DENV epidemics. The results showed a more efficient replicative fitness of L1 over L6 in mosquit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 41 publications
(60 reference statements)
0
22
0
Order By: Relevance
“…During the introduction of DENV-1 in 1994, Panamanian DENV-1 strains from 1995–1999 were grouped into one cluster closely related to isolates detected previously (1993) in Puerto Rico (Figure 2). Only one Panamanian isolate from 1998 clustered with Caribbean and Central American strains (Costa Rica 1993 and Puerto Rico 1996), suggesting possible co-circulation of two clusters of DENV-1 from L1, genotype V. However, several Panamanian DENV-1 strains sampled in 2004 were related to Nicaraguan and Mexican strains sampled in 2004–2006 and 2006–2008, respectively, and contained an amino acid substitution (M297T), which was previously described in L6 [16,32,33,34,35].…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…During the introduction of DENV-1 in 1994, Panamanian DENV-1 strains from 1995–1999 were grouped into one cluster closely related to isolates detected previously (1993) in Puerto Rico (Figure 2). Only one Panamanian isolate from 1998 clustered with Caribbean and Central American strains (Costa Rica 1993 and Puerto Rico 1996), suggesting possible co-circulation of two clusters of DENV-1 from L1, genotype V. However, several Panamanian DENV-1 strains sampled in 2004 were related to Nicaraguan and Mexican strains sampled in 2004–2006 and 2006–2008, respectively, and contained an amino acid substitution (M297T), which was previously described in L6 [16,32,33,34,35].…”
Section: Resultsmentioning
confidence: 81%
“…DENV-1 serotype has five genotypes (I to V) [15,32]. DENV-1 genotype V has been divided into three lineages (L1, L3, L6), with L1 and L6 being the most described in the Americas [16,32,33,34,35]. All sequenced Panamanian DENV-1 isolates were from genotype V, and most of them had signature amino acids of L1 [34,35], although they could be grouped into different clusters (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If genotype replacement does occur, it will be important to see whether existing diagnostic measures work as well for the new genotype as those measures did for the previous genotype, whether the new genotype causes a larger outbreak than the previous one, and whether the disease severity changes. However, the genotype replacement of DENV may not necessarily follow automatically after the introduction of the new lineage; indeed there is precedent (in Brazil) for the failure of a newly introduced DENV-1 lineage to replace a pre-existing lineage of DENV-1 [ 71 ]. Our phylogeographic analysis also suggested repeated introduction of DENV-2 genotype Cosmopolitan into Thailand without detectable outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that viral evolution plays an important role in determining whether a person develops severe dengue disease 67. It is not yet understood how the strain of virus influences ADE, if at all, but the strain is an important risk factor influencing viraemia levels, infectivity in mosquitoes, and epidemic potential, all of which influence transmission dynamics.…”
Section: Yes—duane J Gublermentioning
confidence: 99%